Efficient carrier multiplication in CsPbI3 perovskite nanocrystals. Issue 1 (December 2018) - Weerd, Chris; Gomez, Leyre; Capretti, Antonio; Lebrun, Delphine; Matsubara, Eiichi; Lin, Junhao; Ashida, Masaaki; Spoor, Frank; Siebbeles, Laurens; Houtepen, Arjan; Suenaga, Kazutomo; Fujiwara, Yasufumi; et al.
Abstract The all-inorganic perovskite nanocrystals are currently in the research spotlight owing to their physical stability and superior optical properties—these features make them interesting for optoelectronic and photovoltaic applications. Here, we report on the observation of highly efficient carrier multiplication in colloidal CsPbI3 nanocrystals prepared by a hot-injection method. The carrier multiplication process counteracts thermalization of hot carriers and as such provides the potential to increase the conversion efficiency of solar cells. We demonstrate that carrier multiplication commences at the threshold excitation energy near the energy conservation limit of twice the band gap, and has step-like characteristics with an extremely high quantum yield of up to 98%. Using ultrahigh temporal resolution, we show that carrier multiplication induces a longer build-up of the free carrier concentration, thus providing important insights into the physical mechanism responsible for this phenomenon. The evidence is obtained using three independent experimental approaches, and is conclusive. In semiconductor nanocrystals, efficient carrier multiplication counteracts hot carrier thermalization, increasing the overall carrier generation yield. Here, de Weerd et al. observe a quantum yield of up to 98% in CsPbI3 nanocrystals as a result of efficient carrier multiplication.